Peranan Instrumen Kebijakan Moneter Syariah Terhadap Pertumbuhan Ekonomi Di Sumatera Utara Periode 2012-2021 - Ayu Syafitri Sinaga, Ahmad Fuadi, Asmawarna Sinaga (Islamic Education Journal, 2022)
This study aims to determine the role of sharia monetary policy instruments on economic growth in North Sumatra. The Islamic monetary policy instrument is in the form of economic growth in North Sumatra using the Gross Regional Domestic Product (GRDP). In this study, Islamic monetary policy instruments focused on Bank Indonesia Sharia Certificates (SBIS) and Bank Indonesia Sharia Deposit Facilities (FASBIS), while economic growth in North Sumatra used the Gross Regional Domestic Product (GDP). This type of research is quantitative research that emphasizes numerical data (numbers) processed using inferential statistical methods (analyzing the relationship between variables by testing hypotheses). The results of the study explain that Islamic monetary policy instruments (SBIS and FASBIS) have on economic growth in North Sumatra (GRDP) for the 2012-2021 period. This can be seen from the hypothesis test, namely the f test which shows that the Fcount value is 0.041 with a significance value of 0.000. Because the significance value is less than 0.05 (0.041 <0.05) and the value of Fcount > Ftable (4.679 > 4.46), the independent variables simultaneously affect the dependent variable. Islamic monetary policy instruments (SBIS and FASBIS) affect economic growth in North Sumatra (GRDP) by 45%. The coefficient is positive or in line between Islamic monetary policy (SBIS and FASBIS) has increased, so economic growth in North Sumatra (GDP).